Regional Dimensions of Liability of Foreignness: Between a Rock and a Hard Place? - Wolfgang Sofka; Jörg Zimmermann (Max Planck Institute of Economics, 2007)
In this paper we develop optimized localization strategies for multinational firms to overcome their liability of foreignness by adding a regional dimension. We explore conceptually whether economic stress in a region has a mitigating or reinforcing effect. We test this analytical framework empirically on the highly internationalized German car market and find that economically depressed regions are promising stepping stones into foreign markets.
Keywords: 330; Liability of foreignness; multinational strategy; automotive market; Multinationales Unternehmen; Standortwahl; Internationale Markteintrittsstrategie; Strukturschwacher Raum; Kraftfahrzeugindustrie; Deutschland; Alte Bundesländer; Neue Bundesländer